2006
DOI: 10.1002/ccd.20833
|View full text |Cite
|
Sign up to set email alerts
|

Improved survival with drug‐eluting stent implantation in comparison with bare metal stent in patients with severe left ventricular dysfunction

Abstract: Compared with bare-metal stents, DES implantation reduces mortality and MACE in high risk patients with severe left ventricular dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 31 publications
0
9
1
4
Order By: Relevance
“…While there is extensive data [1][2][3][4][5][6][7][8][9][10][11][12][13] demonstrating a low TVR in patients with preserved LV function, there are limited reports [14] demonstrating a low TVR in those with poor LV dysfunction. Eight patients (6%) of our DES cohort did require repeat nontarget vessel intervention in a vessel other than the index artery, probably reflecting a less complete initial revascularization (in fact only half the diseased arteries were treated by the interventionalist).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While there is extensive data [1][2][3][4][5][6][7][8][9][10][11][12][13] demonstrating a low TVR in patients with preserved LV function, there are limited reports [14] demonstrating a low TVR in those with poor LV dysfunction. Eight patients (6%) of our DES cohort did require repeat nontarget vessel intervention in a vessel other than the index artery, probably reflecting a less complete initial revascularization (in fact only half the diseased arteries were treated by the interventionalist).…”
Section: Discussionmentioning
confidence: 99%
“…These new stents have been shown to be superior to bare metal stent in many clinical condition, including diabetes, in-stent restenosis, long lesions, chronic totally occlusion, left main disease, and small vessels [4][5][6][7][8][9][10][11][12][13]. A recent report from our group suggests that drug-eluting stent use in selected groups of patients with severe left ventricular (LV) dysfunction may improve survival as compared with bare-metal stent [14]. The use of sirolimus-eluting stents in patients with multivessel disease has been reported by the ARTS 2 investigators [7].…”
Section: Introductionmentioning
confidence: 98%
“…Despite the growing evidence of the benefits of DES in several subsets of lesions [4][5][6][7][8][9][10] and patients [11][12][13][14], very few data are available on the benefit of DES in saphenous vein grafts (SVG) over the long term. A recent small prospective randomized trial between the Sirolimus-eluting (SES) stent and BMS [15] reported a significant reduction of late lumen loss, restenosis and repeat target lesion and vessel revascularization at 6 months with SES.…”
Section: Introductionmentioning
confidence: 99%
“…Gioia G y cols suggest that patients with acute ventricular dysfunction should be deemed a high risk population and precisely for this reason. Implementation of a drug-coated stent is advisable since those stents would decrease the incidence of cardiac adverse effects [32] . In our study, we observed a higher restenosis rate and the appearance of new ischemic coronary events in individuals who presented a more reduced LVEF.…”
Section: Discussionmentioning
confidence: 99%